Robótica educativa y pensamiento computacional - Acuña Zúñiga, Ana Lourdes (2022)
The presence of new technologies in the classroom presumes the design and practice of interdisciplinary learning environments where students acquire skills to structure research and solve concrete problems, as well as abilities to acquire new concepts and to respond efficiently to the changing environments of today's world.  Educational Robotics as a learning resource and the promotion of Computational Thinking skills constitute an opportunity to open strategic learning spaces, where the youth of today are trained for the needs and challenges of tomorrow; so that they take the leadership and control of their own process and do it successfully and responsibly with their context, their person and their country.